Conversations with Paul Auster - Auster, Paul, 1947- (Book collections on Project MUSE., 2013)
Paul Auster is one of the most critically acclaimed and intensely studied authors in the early twenty-first century in America. His varied career as a novelist, poet, translator, and filmmaker has attracted scholarly scrutiny from a variety of critical perspectives. The steadily rising arc of his large readership has made him something of a popular culture figure with many appearances in print interviews, as well as on television, the radio, and the Internet. Auster's best known novel may be his first, City of Glass (1985), a grim and intellectually puzzling mystery that belies its surface image as a "detective novel" and goes on to become a profound meditation on transience and mortality, the inadequacies of language, and isolation. Fifteen more novels have followed since then, including The Music of Chance, Moon Palace, The Book of Illusions, and The Brooklyn Follies. He has, in the words of one critic, "given the phrase 'experimental fiction' a good name" by fashioning bona fide literary works with all the rigor and intellect demanded of the contemporary avant-garde. This book will be useful to both scholars and students for the penetrating self-analysis and the wide range of biographical information and critical commentary it contains.